A high-strength low-modulus metastable beta titanium alloy (Ti-29) and a method of making the same
Patent Information
- Application Number
- CN202610912232.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]本发明的目的在于克服现有技术缺陷,提供一种高强度低模量钛合金及其制备方法,解决传统钛合金模量过高、应力屏蔽严重,以及现有低模量钛合金强度不足、强度模量匹配性差、制备工艺复杂的技术难题
1、强模量匹配性极佳:本发明钛合金弹性模量可稳定控制在50~60GPa,接近人体骨骼模量,降低医用植入体的应力屏蔽效应;同时在超低模量基础上实现抗拉强度≥800MPa的高屈服强度,解决了传统低模量钛合金强度不足、承载能力差的核心难题,兼顾适配性与结构承载性能,显著提升临床使用安全性与寿命。
Smart Images

Figure CN122879549A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of titanium alloy materials and relates to a high-strength, low-modulus metastable β titanium alloy (Ti-29) and its preparation method. Specifically, it relates to a titanium alloy that has high strength, low modulus and high plasticity in a wide temperature range (-60~200℃) and its preparation method, which is suitable for biomedical implants, medical devices, aerospace, precision instruments and other fields. Background Technology
[0002] Titanium alloys, with their advantages of low density, high specific strength, excellent corrosion resistance, and good biocompatibility, are widely used in core fields such as aerospace, medical devices, marine engineering, and precision equipment. Traditional commercial titanium alloys, such as pure titanium, TC4, and TC4ELI, generally have an elastic modulus of 100–118 GPa, which is much higher than the elastic modulus of human bone (10–30 GPa). After implantation, they are prone to causing stress shielding effects, inhibiting bone growth and repair, and long-term use can easily lead to bone resorption, implant loosening and falling out, significantly reducing the lifespan of implanted devices and clinical safety. In the aerospace and precision instrument fields, high-modulus titanium alloys have excessively high rigidity and poor toughness matching, which can easily lead to defects such as structural stress concentration and fatigue cracking, failing to meet the requirements of lightweight, high toughness, and high adaptability for high-end equipment.
[0003] Existing low-modulus titanium alloys are mostly based on single Ti-Nb or Ti-Zr systems, and generally suffer from core technological shortcomings: simply pursuing low modulus significantly sacrifices alloy strength, resulting in an inability to simultaneously achieve high strength and low modulus. This leads to problems such as poor compositional stability, imbalance in mechanical properties, complex manufacturing processes, and high mass production costs, making it difficult to simultaneously meet the stringent requirements of low modulus compatibility, high strength load-bearing capacity, and high toughness fatigue resistance, greatly limiting engineering applications. Therefore, developing a high-strength, low-modulus titanium alloy that combines ultra-low modulus, ultra-high strength, excellent toughness, controllable manufacturing processes, and suitability for mass production has significant engineering value and market implications. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a high-strength, low-modulus titanium alloy and its preparation method. This addresses the technical challenges of excessively high modulus and severe stress shielding in traditional titanium alloys, as well as insufficient strength, poor strength-modulus matching, and complex preparation processes in existing low-modulus titanium alloys. This invention, through optimized precise proportioning of multi-element alloys and combined with composite plastic processing and heat treatment processes, overcomes the technical bottleneck of the mutual constraint between low modulus and high strength, obtaining a titanium alloy that combines ultra-low elastic modulus, ultra-high strength, high toughness, and excellent biocompatibility. Furthermore, the preparation process is simple, the performance is highly stable, and it is suitable for industrial mass production.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows: A high-strength, low-modulus metastable β-titanium alloy has the following chemical composition by weight percentage: Nb: 11.0~15.0%; Sn: 10.0~15%; Mo: 0.5~2.0%; Cr: 1.0~3.0%; Zr: 1.0~3.0%; with the balance being Ti and unavoidable impurity elements. Based on d-electron alloy design theory, the average valence electron concentration is 4.15~4.18.
[0006] A method for preparing a high-strength, low-modulus metastable β-titanium alloy includes the following steps: (1) Pressed electrode: using sponge titanium, TiNb master alloy, TiSn master alloy, TiMo master alloy, elemental Cr and sponge zirconium as raw materials, the materials are prepared according to the alloy design composition and pressed into electrodes; (2) Preparation of ingot: The electrode obtained in step (1) was used for three vacuum consumable melting processes. The melting current was 4~10kA and the melting voltage was 28~40V. At the same time, the β transformation temperature of the ingot after melting was measured to be T. β ; (3) High-temperature homogenization treatment: The ingot obtained in step (2) is subjected to high-temperature homogenization treatment at a temperature of T. β + (200~260)℃, heat preservation time 12~24h; (4) Forging: The ingot processed in step (3) is forged in four processes, namely: first forging, temperature T β +(200~260)℃; First single-phase forging, temperature T β + (120~150)℃; Second single-phase forging, temperature T β +(20~50)℃; Finished product forging temperature T β - (30~50)℃; the heat preservation time before forging in each process is 4~8h; the forging deformation in each process is 50~70%; (5) Rolling: The billet obtained in step (4) is rolled at a temperature T β - The rolling process is carried out at (50~80)℃ in one heat, with a cumulative deformation of 70~80% and a holding time of 4~6h; (6) Solution treatment: After the billet obtained in step (5) is kept at a single-phase temperature, it is subjected to water-cooled solution treatment at a holding temperature of T. β + (30~50)℃, heat preservation time is 0.5~1h.
[0007] Further, the pressing voltage of the electrode in step (1) is 150-250 MPa.
[0008] Further, in step (2), the melting current for the first vacuum consumable melting is 4.8~7.6kA, and the melting voltage is 29~33V; the melting current for the second vacuum consumable melting is 5.2~8.8kA, and the melting voltage is 29~36V; the melting current for the third vacuum consumable melting is 5.5~9.0kA, and the melting voltage is 30~36V; after each melting, the electrode is peeled off before the next melting; after the three meltings are completed, the riser and bottom of the ingot are removed after peeling; the peeling thickness is 4-8mm; the β transformation temperature of the ingot is determined by metallographic method, T β =750-820℃.
[0009] Further, in step (4), the first forging is three-stage forging and three-stage drawing; the first single-phase zone forging is three-stage forging and three-stage drawing; the second single-phase zone forging is three-stage forging and three-stage drawing; the finished product forging is drawing and elongation; after each forging process, grinding is performed to ensure that the deformation of each forging process is 50~70%.
[0010] Furthermore, in step (5), after rolling, the skin is peeled and polished.
[0011] Further, after the solution treatment in step (6), room temperature rolling is performed according to the required dimensions to obtain a high-strength, low-modulus metastable β-titanium alloy finished product; the single-pass deformation amount of the room temperature rolling is 5~10%, and the cumulative deformation amount reaches 95%.
[0012] Further, after the solution treatment described in step (6), the billet consists of a single β phase with an elastic modulus of 60~66 GPa; subsequently, it is rolled at room temperature, during which TRIP and TWIP effects are generated, producing stress-induced α″ phase and {332} <113> Twins, the α″ phase has a lower elastic modulus than the matrix β phase, and the introduction of a large number of α″ / β interfaces, twin interfaces and dislocations allows the alloy to obtain high strength without increasing the elastic modulus; the elastic modulus of the finished titanium alloy is 50~60GPa, the yield strength is 730~860MPa, and the tensile strength is 820~900MPa.
[0013] The design concept of this invention is to design a metastable β-titanium alloy using d-electron alloy design theory, which combines the TRIP (transformation-induced plasticity) and TWIP (twin-induced plasticity) effects: First, Nb is selected as the core β-phase stabilizing element, which can effectively reduce the elastic modulus of the titanium alloy while ensuring excellent biocompatibility and corrosion resistance. Second, Sn is added, which can simultaneously improve strength and reduce elastic modulus, and its strengthening effect is higher than that of Nb. Sn also has the effect of inhibiting ω-phase precipitation in the β-phase, thereby stabilizing the β-phase and simultaneously achieving the effects of reducing elastic modulus, improving strength, and reducing cost. Third, Cr is added, which has a high strengthening effect. Cr is a slow eutectoid strong β-stabilizing element, which can significantly strengthen the metastable β-titanium alloy and significantly reduce the Nb content at low addition levels. Fourth, Mo is added, which has a high strengthening effect on β-stabilizing elements, and its strengthening effect is comparable to that of Cr. Finally, Zr is added, which has the effect of inhibiting ω-phase precipitation in the β-phase. The ratio of each element meets the TRIP+TWIP range in the Bo-Md diagram, giving the alloy good processing performance. Furthermore, the interaction between multiple elements results in a strengthening effect greater than the sum of the strengthening effects of a single element, overcoming the traditional problem of inverted strength modulus in titanium alloys and achieving a precise balance between high strength and ultra-low modulus. By adjusting the content of each element, the alloy obtains a single β-phase structure after solution treatment, thus simultaneously possessing ultra-low elastic modulus and excellent cold forming ability, further reducing processing costs.
[0014] The advantages and beneficial effects of this invention are: 1. Excellent modulus matching: The elastic modulus of the titanium alloy of this invention can be stably controlled at 50-60 GPa, close to the modulus of human bone, reducing the stress shielding effect of medical implants; at the same time, it achieves a high yield strength of ≥800 MPa on the basis of ultra-low modulus, solving the core problems of insufficient strength and poor load-bearing capacity of traditional low modulus titanium alloys, taking into account both adaptability and structural load-bearing performance, and significantly improving the safety and lifespan of clinical use.
[0015] 2. Excellent and balanced comprehensive mechanical properties: Through the synergistic solid solution strengthening of Nb, Zr, Sn, Mo and Cr multi-element, combined with the optimized solid solution and rolling composite process, the metastable β phase structure of the alloy is precisely controlled, and the matrix strength is greatly improved without increasing the modulus. This achieves a balance of high strength, low modulus and high toughness, solving the technical bottleneck of poor strength-modulus matching and prominent mechanical property shortcomings of existing low modulus titanium alloys.
[0016] 3. The method described in this invention can be used to prepare titanium alloy rods, wires, plates, etc.
[0017] 4. Simple process and controllable cost: It has low high-temperature rheological stress, low resistance to hot forming, and a large hot working window; it has excellent cold forming performance, with a cold deformation capacity of nearly 100%; the overall preparation process is mature and the parameters are controllable, requiring no complex special processing equipment, and can be adapted to large-scale industrial production. Compared with existing high-end low-modulus titanium alloys, the production cost is significantly reduced, and the market application prospects are broad.
[0018] 5. Wide range of applications: It has excellent biocompatibility, mechanical compatibility, corrosion resistance and structural mechanical properties, and can be widely used in medical implants such as artificial bones, joints and dental implants, as well as lightweight structural components for aerospace, precision instruments, and marine corrosion-resistant equipment. Attached Figure Description
[0019] Figure 1 The XRD phase analysis spectra of the slab in the hot-rolled, solution-treated, and cold-rolled states in Example 1 of this invention are shown.
[0020] Figure 2 The images show the metallographic structure of the slab in the hot-rolled, solution-treated, and cold-rolled states in Example 1 of this invention.
[0021] Figure 3 These are the engineering stress-strain curves of the high-strength, low-modulus metastable β-titanium alloy in the hot-rolled state in Examples 1-3 of this invention.
[0022] Figure 4 These are the stress-strain curves of the high-strength, low-modulus metastable β-titanium alloys in the solid solution state and cold-rolled state in Examples 1-3 of this invention.
[0023] Figure 5 These are the tensile engineering stress-strain curves of the high-strength, high-modulus metastable β-titanium alloys in Examples 1 and 2. Detailed Implementation
[0024] To make the objectives, technical solutions, and effects of the present invention clearer and more explicit, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0025] Specific embodiments and comparative examples illustrate and explain the present invention, but should not be used to limit the scope of the invention. Examples 1-3 are alloys obtained by appropriately adjusting the element content and Bo / Md value according to the preparation steps described in the invention.
[0026] Example 1: A high-strength, low-modulus metastable β-titanium alloy (Ti29-1) has the following chemical composition and mass percentages: Nb 15.0%; Sn 10.5%; Mo 1.0%; Cr 2.0%; Zr 3.0%; with the balance being Ti and unavoidable impurities such as O, N, and H. Based on d-electron alloy design theory, the bond order (Bo) is 2.81, the d-orbital energy level (Md) is 2.42, and the average valence electron concentration is 4.16. The preparation steps are as follows: (1) Pressed electrode. Using sponge titanium, TiNb master alloy, TiSn master alloy, TiMo master alloy, elemental Cr, and sponge zirconium as raw materials, the materials are prepared according to the alloy design composition and pressed into electrodes with dimensions of [size missing] at 200 MPa using a THP32-630A multi-functional press. 32 electrodes, each 100mm x 150mm.
[0027] (2) Preparation of ingots. The electrodes obtained in step (1) were melted into ingots using a ZHT-650 vacuum arc furnace. The electrode is 120mm in diameter, the melting current is 7.5kA, and the melting voltage is 33V; The 120mm electrode was peeled (5mm thick) and then remelted. The electrode is 170mm in diameter, the melting current is 8.5kA, and the melting voltage is 34V; The 170mm electrode was stripped and remelted. The ingot was 220mm × 570mm in diameter, and the melting current was 8.8kA, while the melting voltage was 35V. The ingot required uniform melting with a low current. After peeling, ultrasonic testing was performed, and the riser and bottom depths were determined based on the abnormal noise areas identified in the testing results. The riser and bottom of the ingot were then removed. Simultaneously, the β transformation temperature was determined using metallography to be T. β =800±5℃.
[0028] (3) High-temperature homogenization treatment. The qualified ingots obtained in step (2) are subjected to high-temperature homogenization treatment. The temperature is 1000℃ and the holding time is 24h.
[0029] (4) Forging. The ingot processed in step (3) is subjected to a first-stage forging process, with three forging passes and three drawing passes at a temperature of 1000℃ and a holding time of 8 hours. The size of the forged ingot is 260mm×260mm×300mm. The single-phase zone forging process is performed with three forging passes and three drawing passes at a temperature of 920℃ and a holding time of 6 hours. The size of the forged ingot is 260mm×260mm×290mm. The single-phase zone forging process is performed with three forging passes and three drawing passes at a temperature of 820℃ and a holding time of 4 hours. The size of the forged ingot is 150mm×150mm×860mm. The finished product forging process is performed with drawing passes at a temperature of 770℃ and a holding time of 4 hours. The size of the forged slab is 835mm×215mm×55mm. After each forging process, the slab is ground to ensure that the deformation of each forging process is 60%. The final size of the ground slab is 830mm×210mm×50mm.
[0030] (5) Rolling. The 50mm thick slab obtained in step (4) is hot rolled in the two-phase zone at a temperature of 720℃ for 4 hours, and the cumulative deformation during rolling is 80%. After rolling, the slab is peeled and polished, and the thickness after rolling is 10mm.
[0031] (6) Solution treatment. The slab obtained in step (5) is subjected to water-cooled solution treatment in the single-phase region. The holding temperature is 830℃ and the holding time is 1h, resulting in an easily formable, high-strength, low-modulus metastable β-titanium alloy with an elastic modulus of 61GPa and a yield strength of 670MPa.
[0032] (7) Rolling. The solution-treated slab obtained in step (6) is rolled at room temperature with a single-pass deformation of 5~10%. After 6 passes, it is rolled into a finished plate with a thickness of 7.0 mm. The cumulative deformation is 30%, resulting in an easily formable, high-strength, low-modulus metastable β-titanium alloy with an elastic modulus of 52 GPa and a yield strength of 730 MPa.
[0033] Example 2: A high-strength, low-modulus metastable β-titanium alloy (Ti29-2) has the following chemical composition and mass percentages: Nb 13.0%; Sn 12.5%; Mo 0.8%; Cr 1.5%; Zr 2.0%; with the balance being Ti and unavoidable impurities such as O, N, and H. Based on d-electron alloy design theory, Bo = 2.81, Md = 2.43, and the average valence electron concentration is 4.15. The preparation steps are as follows: (1) Pressed electrode. Using sponge titanium, TiNb master alloy, TiSn master alloy, TiMo master alloy, elemental Cr, and sponge zirconium as raw materials, the materials are prepared according to the alloy design composition and pressed into electrodes with dimensions of [size missing] at 200 MPa using a THP32-630A multi-functional press. 32 electrodes, each 100mm x 150mm.
[0034] (2) Preparation of ingots. The electrodes obtained in step (1) were melted into ingots using a ZHT-650 vacuum arc furnace. The electrode is 120mm in diameter, the melting current is 7.0kA, and the melting voltage is 31V; The 120mm electrode was peeled and remelted. The electrode is 170mm in diameter, the melting current is 8.0kA, and the melting voltage is 32V; The 170mm electrode was stripped and remelted. The ingot was 220mm × 570mm in diameter, with a melting current of 8.5kA and a melting voltage of 34V. The ingot required uniform melting using a low current. After peeling, ultrasonic testing was performed, and the riser and bottom depths were determined based on the abnormal noise areas identified in the testing results. The riser and bottom of the ingot were then removed. Simultaneously, the β transformation temperature was determined using metallography to be T. β =780±5℃.
[0035] (3) High-temperature homogenization treatment. The qualified ingots obtained in step (2) are subjected to high-temperature homogenization treatment. The temperature is 980℃ and the holding time is 24h.
[0036] (4) Forging. The ingot processed in step (3) is subjected to a first forging process, with three forging passes and three drawing passes at a temperature of 980℃ and a holding time of 8 hours. The size of the forged ingot is 260mm×260mm×300mm. The single-phase zone forging process is performed with three forging passes and three drawing passes at a temperature of 900℃ and a holding time of 6 hours. The size of the forged ingot is 260mm×260mm×290mm. The single-phase zone forging process is performed with three forging passes and three drawing passes at a temperature of 800℃ and a holding time of 4 hours. The size of the forged ingot is 150mm×150mm×860mm. The finished product forging process is performed with drawing passes at a temperature of 750℃ and a holding time of 4 hours. The size of the forged slab is 835mm×215mm×55mm. After each forging process, the slab is ground to ensure that the deformation of each forging process is 60%. The final size of the ground slab is 830mm×210mm×50mm.
[0037] (5) Rolling. The 50mm thick slab obtained in step (4) is hot rolled in the two-phase zone at a temperature of 700℃ for 4 hours, and the cumulative deformation during rolling is 80%. After rolling, the slab is peeled and polished, and the thickness after rolling is 10mm.
[0038] (6) Solution treatment. The slab obtained in step (5) is subjected to water-cooled solution treatment in the single-phase region. The holding temperature is 810℃ and the holding time is 1h, resulting in an easily formable, high-strength, low-modulus metastable β-titanium alloy with an elastic modulus of 55GPa and a yield strength of 650MPa.
[0039] (7) Rolling. The solution-treated slab obtained in step (6) is rolled at room temperature with a single-pass deformation of 5~10%. After 6 passes, it is rolled into a finished plate with a thickness of 7.0 mm. The cumulative deformation is 30%, resulting in an easily formable, high-strength, low-modulus metastable β-titanium alloy with an elastic modulus of 64 GPa and a yield strength of 680 MPa.
[0040] Example 3: A high-strength, low-modulus metastable β-titanium alloy (Ti29-3) has the following chemical composition and mass percentages: Nb 11.0%; Sn 14.5%; Mo 1.5%; Cr 2.5%; Zr 1.0%; with the balance being Ti and unavoidable impurities such as O, N, and H. Based on d-electron alloy design theory, Bo = 2.81, Md = 2.43, and the average valence electron concentration is 4.17. The preparation steps are as follows: (1) Pressed electrode. Using sponge titanium, TiNb master alloy, TiSn master alloy, TiMo master alloy, elemental Cr, and sponge zirconium as raw materials, the materials are prepared according to the alloy design composition and pressed into electrodes with dimensions of [size missing] at 200 MPa using a THP32-630A multi-functional press. 32 electrodes, each 100mm x 150mm.
[0041] (2) Preparation of ingots. The electrodes obtained in step (1) were melted into ingots using a ZHT-650 vacuum arc furnace. The electrode is 120mm in diameter, the melting current is 6.5kA, and the melting voltage is 30V; The 120mm electrode was peeled and remelted. The electrode is 170mm in diameter, the melting current is 7.5kA, and the melting voltage is 31V; The 170mm electrode was stripped and remelted. A 220mm × 570mm ingot was cast using a melting current of 8kA and a melting voltage of 33V. The ingot was required to be melted uniformly using a low current. After peeling, ultrasonic testing was performed, and the riser and bottom depths of the ingot were determined based on the abnormal noise areas identified in the testing results. The riser and bottom of the ingot were then removed. Simultaneously, the β transformation temperature was determined using metallography to be T. β =760±5℃.
[0042] (3) High-temperature homogenization treatment. The qualified ingots obtained in step (2) are subjected to high-temperature homogenization treatment. The temperature is 960℃ and the holding time is 24h.
[0043] (4) Forging. The ingot processed in step (3) is subjected to a first-stage forging process, with three forging passes at 960℃ and a holding time of 8 hours. The size of the forged ingot is 260mm×260mm×300mm. The single-phase zone forging process is performed with three forging passes at 880℃ and a holding time of 6 hours. The size of the forged ingot is 260mm×260mm×290mm. The single-phase zone forging process is performed with three forging passes at 780℃ and a holding time of 4 hours. The size of the forged ingot is 150mm×150mm×860mm. The finished product forging process is performed with drawing at 730℃ and a holding time of 4 hours. The size of the forged slab is 835mm×215mm×55mm. After each forging process, the slab is ground to ensure that the deformation of each forging process is 60%. The final size of the ground slab is 830mm×210mm×50mm.
[0044] (5) Rolling. The 50mm thick slab obtained in step (4) is hot rolled in the two-phase zone at a temperature of 680℃ for 4 hours, and the cumulative deformation during rolling is 80%. After rolling, the slab is peeled and polished, and the thickness after rolling is 10mm.
[0045] (6) Solution treatment. The slab obtained in step (5) is subjected to water-cooled solution treatment in the single-phase region. The holding temperature is 790℃ and the holding time is 1h, resulting in an easily formable, high-strength, low-modulus metastable β-titanium alloy with an elastic modulus of 66GPa and a yield strength of 700MPa.
[0046] (7) Rolling. The solution-treated slab obtained in step (6) is rolled at room temperature with a single-pass deformation of 5~10%. After 6 passes, it is rolled into a finished plate with a thickness of 7.0 mm. The cumulative deformation is 30%, resulting in an easily formable, high-strength, low-modulus metastable β-titanium alloy with an elastic modulus of 53 GPa and a yield strength of 860 MPa.
[0047] The hot-rolled slab obtained at the end of step (5), the solution-treated slab obtained at the end of step (6), and the cold-rolled slab finally prepared in step (7) of Examples 1-3 were subjected to room temperature tensile mechanical property tests (the test standard is GB / T228.1-2021 "Metallic materials, tensile testing - Part 1: Room temperature test method"). The test results are shown in Tables 1, 2 and 3.
[0048] Table 1. Room temperature tensile mechanical properties of hot-rolled Examples 1-3
[0049] Table 2. Room temperature tensile mechanical properties of solid solution-treated Examples 1-3
[0050] Table 3. Room temperature tensile mechanical properties of cold-rolled Examples 1-3
[0051] As can be seen from the results in Tables 1-3, the alloys in Examples 1-3 have both high strength and low elastic modulus, and their low yield strength in the solid solution state is beneficial for molding.
[0052] Figure 1 These are the XRD phase analysis spectra of the hot-rolled, solution-treated, and cold-rolled states in Example 1 of this invention. Figure 2 These are metallographic microstructure images of the hot-rolled, solution-treated, and cold-rolled states in Embodiment 1 of this invention. Combined with... Figure 1 and Figure 2 It can be seen that after solid solution treatment in the single-phase region, the alloy is composed of a single β phase with a fine and uniform equiaxed crystal structure; after cold rolling, a large number of long needle-shaped stress-induced martensite α″ phases are generated. Figure 3 and Figure 4 These are the tensile engineering stress-strain curves of the high-strength, low-modulus metastable β-titanium alloys obtained in Examples 1, 2, and 3 of this invention after hot rolling, solution treatment, and cold rolling. It can be seen that after solution treatment, the alloy has a low elastic modulus, approximately 60-66 GPa, while its yield strength is as high as 670-700 MPa; after cold rolling, the alloy's elastic modulus decreases to 52-60 GPa, its yield strength further increases to 730-860 MPa, and its tensile strength increases to 820-900 MPa.
[0053] The results of the examples show that the present invention can produce high-strength, low-modulus metastable β-titanium alloys through cold forming, which greatly reduces the hot working process, expands the processing window of titanium alloy materials, reduces production costs, and thus realizes the engineering application of new materials.
[0054] Comparative Example 1: A high-strength, high-modulus metastable β-titanium alloy has the same chemical composition and mass percentage as in Example 2, specifically: Nb 13.0%; Sn 12.5%; Mo 0.8%; Cr 1.5%; Zr 2.0%; the balance being Ti and unavoidable impurities such as O, N, and H; Bo = 2.81, Md = 2.43, and the average valence electron concentration is 4.15. The preparation steps are as follows: (1) Pressed electrode. Using sponge titanium, TiNb master alloy, TiSn master alloy, TiMo master alloy, elemental Cr, and sponge zirconium as raw materials, the materials are prepared according to the alloy design composition and pressed into electrodes with dimensions of [size missing] at 200 MPa using a THP32-630A multi-functional press. 32 electrodes, each 100mm x 150mm.
[0055] (2) Preparation of ingots. The electrodes obtained in step (1) were melted into ingots using a ZHT-650 vacuum arc furnace. The electrode is 120mm in diameter, the melting current is 7.0kA, and the melting voltage is 31V; The 120mm electrode was peeled and remelted. The electrode is 170mm in diameter, the melting current is 8.0kA, and the melting voltage is 32V; The 170mm electrode was stripped and remelted. The ingot was 220mm × 570mm in diameter, with a melting current of 8.5kA and a melting voltage of 34V. The ingot required uniform melting using a low current. After peeling, ultrasonic testing was performed, and the riser and bottom depths were determined based on the abnormal noise areas identified in the testing results. The riser and bottom of the ingot were then removed. Simultaneously, the β transformation temperature was determined using metallography to be T. β =780±5℃.
[0056] (3) High-temperature homogenization treatment. The qualified ingots obtained in step (2) are subjected to high-temperature homogenization treatment. The temperature is 980℃ and the holding time is 24h.
[0057] (4) Forging. The ingot processed in step (3) is subjected to a first forging process, with three forging passes and three drawing passes at a temperature of 980℃ and a holding time of 8 hours. The size of the forged ingot is 260mm×260mm×300mm. The single-phase zone forging process is performed with three forging passes and three drawing passes at a temperature of 900℃ and a holding time of 6 hours. The size of the forged ingot is 260mm×260mm×290mm. The single-phase zone forging process is performed with three forging passes and three drawing passes at a temperature of 800℃ and a holding time of 4 hours. The size of the forged ingot is 150mm×150mm×860mm. The finished product forging process is performed with drawing passes at a temperature of 750℃ and a holding time of 4 hours. The size of the forged slab is 835mm×215mm×55mm. After each forging process, the slab is ground to ensure that the deformation of each forging process is 60%. The final size of the ground slab is 830mm×210mm×50mm.
[0058] (5) Rolling. The 50mm thick slab obtained in step (4) is hot rolled in the two-phase zone at a temperature of 700℃ for 4 hours, and the cumulative deformation during rolling is 80%. After rolling, the slab is peeled and polished, and the thickness after rolling is 10mm.
[0059] (6) Annealing treatment. The slab obtained in step (5) is subjected to air-cooled annealing treatment in the two-phase region. The holding temperature is 650℃ and the holding time is 2h, resulting in a high-strength, high-modulus metastable β-titanium alloy with an elastic modulus of 74GPa and a yield strength of 710MPa.
[0060] Comparative Example 2: A high-strength, high-modulus metastable β-titanium alloy has the same chemical composition and mass percentage as in Example 2, specifically: Nb 13.0%; Sn 12.5%; Mo 0.8%; Cr 1.5%; Zr 2.0%; the balance being Ti and unavoidable impurities such as O, N, and H; Bo = 2.81, Md = 2.43, and the average valence electron concentration is 4.15. The preparation steps are as follows: (1) Pressed electrode. Using sponge titanium, TiNb master alloy, TiSn master alloy, TiMo master alloy, elemental Cr, and sponge zirconium as raw materials, the materials are prepared according to the alloy design composition and pressed into electrodes with dimensions of [size missing] at 200 MPa using a THP32-630A multi-functional press. 32 electrodes, each 100mm x 150mm.
[0061] (2) Preparation of ingots. The electrodes obtained in step (1) were melted into ingots using a ZHT-650 vacuum arc furnace. The electrode is 120mm in diameter, the melting current is 7.0kA, and the melting voltage is 31V; The 120mm electrode was peeled and remelted. The electrode is 170mm in diameter, the melting current is 8.0kA, and the melting voltage is 32V; The 170mm electrode was stripped and remelted. The ingot was 220mm × 570mm in diameter, with a melting current of 8.5kA and a melting voltage of 34V. The ingot required uniform melting using a low current. After peeling, ultrasonic testing was performed, and the riser and bottom depths were determined based on the abnormal noise areas identified in the testing results. The riser and bottom of the ingot were then removed. Simultaneously, the β transformation temperature was determined using metallography to be T. β =780±5℃.
[0062] (3) High-temperature homogenization treatment. The qualified ingots obtained in step (2) are subjected to high-temperature homogenization treatment. The temperature is 980℃ and the holding time is 24h.
[0063] (4) Forging. The ingot processed in step (3) is subjected to a first forging process, with three forging passes and three drawing passes at a temperature of 980℃ and a holding time of 8 hours. The size of the forged ingot is 260mm×260mm×300mm. The single-phase zone forging process is performed with three forging passes and three drawing passes at a temperature of 900℃ and a holding time of 6 hours. The size of the forged ingot is 260mm×260mm×290mm. The single-phase zone forging process is performed with three forging passes and three drawing passes at a temperature of 800℃ and a holding time of 4 hours. The size of the forged ingot is 150mm×150mm×860mm. The finished product forging process is performed with drawing passes at a temperature of 750℃ and a holding time of 4 hours. The size of the forged slab is 835mm×215mm×55mm. After each forging process, the slab is ground to ensure that the deformation of each forging process is 60%. The final size of the ground slab is 830mm×210mm×50mm.
[0064] (5) Rolling. The 50mm thick slab obtained in step (4) is hot rolled in the two-phase zone at a temperature of 700℃ for 4 hours, and the cumulative deformation during rolling is 80%. After rolling, the slab is peeled and polished, and the thickness after rolling is 10mm.
[0065] (6) Annealing treatment. The slab obtained in step (5) is subjected to air-cooled annealing treatment in the two-phase region. The holding temperature is 600℃ and the holding time is 2h, resulting in a high-strength, high-modulus metastable β-titanium alloy with an elastic modulus of 81GPa and a yield strength of 740MPa.
[0066] The annealed slabs obtained after step (6) in Comparative Examples 1-2 were subjected to room temperature tensile mechanical property tests (the test standard was GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Room temperature test method"). The test results are shown in Table 4.
[0067] Table 4. Room temperature tensile mechanical properties of comparative examples 1-2 in the annealed state
[0068] As can be seen from the results in Table 4, the metastable β-titanium alloys obtained in Comparative Examples 1 and 2 have high strength and high modulus.
[0069] Figure 5 These are the tensile engineering stress-strain curves of the high-strength, high-modulus metastable β-titanium alloys obtained after two-phase region annealing in Comparative Examples 1 and 2 of this invention. It can be seen that after two-phase region annealing, the alloy exhibits a high elastic modulus of approximately 74-81 GPa, and also a high yield strength of approximately 710-740 MPa.
[0070] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A high-strength, low-modulus metastable β-titanium alloy, characterized in that, The chemical composition of this titanium alloy, by weight percentage, is Nb: 11.0~15.0%; Sn: 10.0~15%; Mo: 0.5~2.0%; Cr: 1.0~3.0%; Zr: 1.0~3.0%; balance is Ti and unavoidable impurity elements; based on d-electron alloy design theory, the average valence electron concentration is 4.15~4.
18.
2. A method for preparing the high-strength, low-modulus metastable β-titanium alloy according to claim 1, characterized in that, Includes the following steps: (1) Pressed electrode: using sponge titanium, TiNb master alloy, TiSn master alloy, TiMo master alloy, elemental Cr and sponge zirconium as raw materials, the materials are prepared according to the alloy design composition and pressed into electrodes; (2) Preparation of ingot: The electrode obtained in step (1) was used for three vacuum consumable melting processes. The melting current was 4~10kA and the melting voltage was 28~40V. At the same time, the β transformation temperature of the ingot after melting was measured to be T. β ; (3) High-temperature homogenization treatment: The ingot obtained in step (2) is subjected to high-temperature homogenization treatment at a temperature of T. β + (200~260)℃, heat preservation time 12~24h; (4) Forging: The ingot processed in step (3) is forged in four processes, namely: first forging, temperature T β +(200~260)℃; First single-phase forging, temperature T β + (120~150)℃; Second single-phase forging, temperature T β +(20~50)℃; Finished product forging temperature T β - (30~50)℃; the heat preservation time before forging in each process is 4~8h; the forging deformation in each process is 50~70%; (5) Rolling: The billet obtained in step (4) is rolled at a temperature T β - The rolling process is carried out at (50~80)℃ in one heat, with a cumulative deformation of 70~80% and a holding time of 4~6h; (6) Solution treatment: After the billet obtained in step (5) is kept at a single-phase temperature, it is subjected to water-cooled solution treatment at a holding temperature of T. β + (30~50)℃, heat preservation time is 0.5~1h.
3. The method for preparing the high-strength, low-modulus metastable β-titanium alloy according to claim 2, characterized in that, The pressing voltage of the electrode in step (1) is 150-250 MPa.
4. The method for preparing the high-strength, low-modulus metastable β-titanium alloy according to claim 2, characterized in that, In step (2), the melting current for the first vacuum consumable melting is 4.8~7.6kA and the melting voltage is 29~33V; the melting current for the second vacuum consumable melting is 5.2~8.8kA and the melting voltage is 29~36V; the melting current for the third vacuum consumable melting is 5.5~9.0kA and the melting voltage is 30~36V; after each melting, the electrode is peeled off before the next melting; after the three meltings are completed, the riser and bottom of the ingot are removed after peeling; the peeling thickness is 4-8mm; the β transformation temperature of the ingot is determined by metallographic method, T β =750-820℃.
5. The method for preparing the high-strength, low-modulus metastable β-titanium alloy according to claim 2, characterized in that: In step (4), the first forging is three-stage forging and three-stage drawing; the first single-phase zone forging is three-stage forging and three-stage drawing; the second single-phase zone forging is three-stage forging and three-stage drawing; the finished product forging is drawing and elongation; after each forging process, grinding is performed to ensure that the deformation of each forging process is 50~70%.
6. The method for preparing the high-strength, low-modulus metastable β-titanium alloy according to claim 2, characterized in that: In step (5), after rolling, the skin is peeled and polished.
7. The method for preparing the high-strength, low-modulus metastable β-titanium alloy according to claim 2, characterized in that, After the solution treatment in step (6), room temperature rolling is performed according to the required dimensions to obtain a high-strength, low-modulus metastable β-titanium alloy finished product; the single-pass deformation amount of the room temperature rolling is 5~10%, and the cumulative deformation amount reaches 95%.
8. The method for preparing the high-strength, low-modulus metastable β-titanium alloy according to claims 2-7, characterized in that, After the solution treatment described in step (6), the billet consists of a single β phase with an elastic modulus of 60~66 GPa; subsequently, it is rolled at room temperature, during which TRIP and TWIP effects are generated, producing stress-induced α″ phase and {332} <113> Twins, the α″ phase has a lower elastic modulus than the matrix β phase, and the introduction of a large number of α″ / β interfaces, twin interfaces and dislocations allows the alloy to obtain high strength without increasing the elastic modulus; the elastic modulus of the finished titanium alloy is 50~60GPa, the yield strength is 730~860MPa, and the tensile strength is 820~900MPa.